Pengembangan Keterampilan Pembacaan Sholawat Ad-Diba'iyah dan Seni Hadroh Al-Banjari di TPQ Al-Furqon Desa Jatiwates - Siti Sufaidah; Nurul Yaqin; Moh. Danur Wenda; Solihatuni'mah Solihatuni'mah; Ica Nini Wulandari (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Diba'an is an art tradition of reading and chanting sholawat to the Prophet Muhammad SAW which is generally accompanied by hadrah music. This activity is carried out by Muslims with the aim of getting closer to Allah. The purpose of this activity is to have a positive influence on the development of the quality, skills and abilities of students in TPQ Al-Furqon related to the Training of Reading Maulid Diba'iyah Prayers and the art of hadroh al-banjari. This activity was carried out in October 2022 which was attended by 15 students of TPQ Al-Furqon, Jatiwates Village, Tembelang District, Jombang Regency. The training activities use the Participatory Action Research method. The final result of the study showed that the skills and understanding of the students increased after the training activities were held. Keywords: Diba'an; Hadrah; Students,;TPQ Al-Furqon